THE INTERNAL AUDIT EFFECTIVENESS OF PUBLIC LIMITED COMPANIES IN CAMEROON: A STUDY OF ITS DETERMINANTS (Journal of Business Management and Accounting, 2026)
Internal audit effectiveness plays a crucial role in enhancing corporate governance, financial transparency, and risk management, yet its determinants remain a subject of debate, especially in developing economies. This study examines the key factors influencing internal audit effectiveness in public limited companies across the three regions of Cameroon. Using a quantitative research approach, data were collected through structured questionnaires from 60 public limited companies operating in these three regions. The ordinary least squares enable us to highlight that the relationship between internal and external auditors and the outsourcing of internal audit functions significantly enhance internal audit effectiveness, supporting the agency theory by demonstrating the value of independent monitoring mechanisms. However, the size of the internal audit team, the presence of an internal control system, board independence, and CEO duality do not exhibit a significant effect, suggesting that audit quality depends more on governance structures, enforcement mechanisms, and auditor competence rather than these traditional factors. These results have important implications for corporate governance in Cameroon, pointing out that it's necessary to improve coordination between auditors, strategic outsourcing, and stronger regulatory enforcement rather than merely expanding audit teams or relying on internal controls. The study contributes to the growing body of literature on internal auditing in emerging markets and provides recommendations for policymakers, corporate leaders, and future research.
Keywords: Internal audit effectiveness; outsourcing of internal audit functions; size of internal audit team; presence of an internal control system; PLC; Cameroon